Resistance profile of drugs composing the "shorter" regimen for multidrug-resistant tuberculosis in Brazil, 2000–2015. Issue 4 (13th April 2017) - Dalcolmo, Margareth; Gayoso, Regina; Sotgiu, Giovanni; D'Ambrosio, Lia; Rocha, Jorge Luiz; Borga, Liamar; Fandinho, Fatima; Braga, Jose Ueleres; Arakaki Sanchez, Denise; Dockhorn, Fernanda; Centis, Rosella; Migliori, Giovanni Battista
The difficulties in managing multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant (XDR) TB are well known. The regimens are very expensive, often toxic, and require up to 24 months to achieve an acceptable probability of success [1–3]. The first nationwide report on the drug resistance profile of the drugs composing the WHO "shorter" regimen in Brazil http://ow.ly/XfJa3096FsT